Person deixis as a communicative tool in medical consultations - Daniel Many; Katalin Fogarasi; Péter Torzsa (Ibérica)
This study investigates the role of person deixis in enhancing doctor-patient communication. Person deixis, which involves linguistic expressions linking utterances to personal referents, is crucial in shaping the dynamics of medical consultations. Drawing on Functional Pragmatics, this research emphasizes the importance of context and communicative functions in language use. A mixed-method approach was employed, combining quantitative and qualitative analyses of a Hungarian corpus comprising 50 recorded consultations between six general practitioners and their patients. Quantitative analysis revealed that third-person singular verbs, used formally to address patients, are the most frequent type of person deixis, accounting for 37.4% of occurrences. First-person singular verbs (13.9%) and first-person plural verbs (7.4%) also play important roles in conveying personal perspectives and fostering collaboration. Personal pronouns and nouns with possessive suffixes further personalize interactions, emphasizing the patient's active role. Qualitative analysis highlighted how deictic expressions construct identities, and moderate relational dynamics. The use of third-person singular verbs reflects a formal and respectful tone, maintaining professional distance. In contrast, first-person singular and plural verbs enhance patient engagement and collaborative decision-making, fostering a sense of partnership and empathy. The findings demonstrate a communication style that balances formality and respect with active participation and collaboration. Understanding these patterns can inform best practices for enhancing healthcare communication, ultimately improving patient outcomes and satisfaction.